Determination of soil specific surface area by water vapor adsorption: III Comparison of surface areas determined by water vapor and nitrogen gas adsorption - Niskanen, Raina; Mäntylahti, Väinö (Agricultural and Food Science, 1988)
The specific surface areas of ten soil samples (clay content 1—72 %, organic carbon content 0.8—11.5 %) were determined by water vapor and nitrogen gas adsorption. The surface areas obtained by application of the BET equation to water vapor sorption at p/po 0.12—0.42 (21—195 m2/g) were, on the average, 80 % of the areas determined by water vapor sorption at p/po 0.20, range 27—229 m2/g. A BET water monolayer coverage was formed on the soil surface at p/po 0.12—0.20. The BET water area correlated closely with the one-point water area (p/po 0.20). The surface area determined by nitrogen gas adsorption ranged from 0.3 to 21 m2/g and did not correlate closely with water areas. The water surface areas were closely related to soil organic carbon content, while the nitrogen area was primarily related to soil clay content.